Shoah e Literatura de Testemunho: O campo concentracionário enquanto lugar de memória - Roberto, Isabella Alessandra Cortada (CEM – Cultura, Espaço & Memória, 2021)
To remember and to forget are actions that involve selection of information, which means that it is impossible to remember without forgetting. Being the collective memory a social construct and a factor of identity for any community, how are we supposed to live with forgetfulness? How are we to live upon the deletion of the past (de-memorizing)? To counteract the silences and the unsaid it is possible to think of underground memories that express the spoken word of the excluded and the neglected from the official memory. Shaping a new writing and a new literature, innumerous authors consecrated thus their experiences of pain and trauma caused by Shoah. It is their examples of life and writing that we bring forward into confrontation, resorting to a conceptual frame that will also be supported by such thinkers as Michael Pollack, Theodor Adorno, Giorgio Agamben, Hannah Arendt or Walter Benjamin.